Progress and Perspectives on Covalent‐Organic Frameworks (COFs) and Composites for Various Energy Applications. Issue 55 (11th August 2021) - Kumar, Ravinder; Naz Ansari, Shagufi; Deka, Rakesh; Kumar, Praveen; Saraf, Mohit; Mobin, Shaikh M.
Abstract: Covalent‐organic frameworks (COFs), being a new member of the crystalline porous materials family, have emerged as important materials for energy storage/conversion/generation devices. They possess high surface areas, ordered micro/mesopores, designable structures and an ability to precisely control electro‐active groups in their pores, which broaden their application window. Thanks to their low weight density, long range crystallinity, reticular nature and tunable synthesis approach towards two and three dimensional (2D and 3D) networks, they have been found suitable for a range of challenging electrochemical applications. Our review focuses on the progress made on the design, synthesis and structure of COFs and their composites for various energy applications, such as metal‐ion batteries, supercapacitors, water‐splitting and solar cells. Additionally, attempts have been made to correlate the structural and mechanistic characteristics of COFs with their applications. Abstract : Covalent‐organic frameworks (COFs) outline a resourceful illustration by uniting the remarkable properties of materials such as structural and chemical modulation, porosity and crystallinity, which can be productive for different types of metal‐ion batteries, supercapacitors, water splitting (Hydrogen evolution reaction, HER and Oxygen evolution reaction, OER) and solar cells.